The Influence of the Introduction to School Field (PLP) II Course and Self-Efficacy on the Interest in Becoming a Teacher among Office Administration Education Students at Medan State University - Sianturi, Santa Lusia; Munajat, Munajat (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the influence of the School Field Introduction Program (PLP) II and self-efficacy on the interest in becoming a teacher among students of the Office Administration Education Study Program, Stambuk 2021, Faculty of Economics, State University of Medan. The background of this study is based on the phenomenon of low interest of education students to become teachers, which is influenced by internal factors such as self-efficacy and external factors such as PLP experience. The research method used is quantitative with data collection through questionnaires to 44 students. The results of the pre-study showed that most students preferred other professions to becoming teachers, and low levels of self-efficacy also influenced this interest. This study is expected to provide theoretical and practical contributions in efforts to increase students' interest in pursuing a career as a teacher by strengthening PLP experience and self-efficacy.